2020
DOI: 10.1101/2020.09.30.20193888
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Associations of diarised sleep onset time, period and duration with total and central adiposity in a biethnic sample of young children: the Born in Bradford study

Abstract: Objectives: To investigate associations of sleep timing, period and duration with total and abdominal adiposity in a biethnic sample of children aged 18 and 36 months (m) Design: Cross-sectional observational study Setting: The Born in Bradford 1000 study, UK Participants: Children aged approximately 18m (n=209; 40.2% South Asian; 59.8% White) and 36m (n=162; 40.7% South Asian; 59.3% White) Primary and secondary outcome measures: Parents completed a 3-day sleep diary from which children's average daily sleep o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Furthermore, it is a limitation that information was not available for potentially key mediating variables, such as unhealthy snacking and meal times. Sleep restriction studies report increased snacking under short sleep conditions, particularly when participants would normally be asleep (Beebe et al, 2013; Nedeltcheva et al, 2009), and an investigation of young children found that an association of later sleep onset with higher adiposity was attenuated when adjusted for timing of the evening meal (Collings et al, 2021). Animal models and clinical trials of adult populations indicate that early and time‐restricted feeding has numerous physiological benefits, including lower adiposity (de Cabo & Mattson, 2019; Sutton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a limitation that information was not available for potentially key mediating variables, such as unhealthy snacking and meal times. Sleep restriction studies report increased snacking under short sleep conditions, particularly when participants would normally be asleep (Beebe et al, 2013; Nedeltcheva et al, 2009), and an investigation of young children found that an association of later sleep onset with higher adiposity was attenuated when adjusted for timing of the evening meal (Collings et al, 2021). Animal models and clinical trials of adult populations indicate that early and time‐restricted feeding has numerous physiological benefits, including lower adiposity (de Cabo & Mattson, 2019; Sutton et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is a limitation that information was not available for potentially key mediating variables such as unhealthy snacking and meal times. Sleep restriction studies report increased snacking under short sleep conditions, particularly when participants would normally be asleep [35, 36], and an investigation of young children found that an association of later sleep onset with higher adiposity was attenuated when adjusted for timing of the evening meal [37]. Animal models and clinical trials of adult populations have further shown that early and time-restricted feeding has numerous physiological benefits, including lower adiposity [38, 39].…”
Section: Discussionmentioning
confidence: 99%